Virgin Coconut Oil: Enzymatic and Acidification Methods for Production – A Review - Harun, Rizqi Fadhilah; Ichwan, Muhammad Maulana; Ardani, Raka; Kusumayanti, Heny (Vocational College of Universitas Diponegoro, 2024)
Making Virgin Coconut Oil (VCO) was an important process in the coconut oil industry, which had potential for medical and beauty applications. This article discussed the method of making VCO using fermentation and enzymatic approaches. Making VCO involved several stages, including making coconut milk, adding ingredients such as pieces of young papaya, pineapple tubers, and yeast tape, and settling and separating the oil liquid. Adding papain and bromelain enzymes in the enzymatic process had been proven to increase the yield of coconut oil compared to fermentation methods without adding enzymes. Enzyme concentration and incubation time influenced the yield of VCO, with increasing enzyme concentration and optimal incubation time increasing oil production. This literature review provided insight into the potential of fermentation and enzymatic methods in VCO production, as well as provided a systematic framework for testing the effectiveness and quality of VCO produced through innovative approaches. The VCO manufacturing method using an enzymatic approach had the potential to increase coconut oil production yields and meet established quality standards.